The Primacy Project: making difficult decisions in the paediatric intensive care unit (PICU) - Ritchie, Dawn (2020)
The predominant end of life scenario within paediatric intensive care units (PICUs) in the developed world results from an active decision to withdraw life sustaining medical treatment. Consideration centres on the problematic concept of whether treatment being provided is no longer in the best interests of the child. The notion of best interests presupposes that there is, theoretically, a definitively right answer to the question “is this intervention in the best interests of the child?” Yet, when making clinical decisions, which have implications for life, quality of life, quality of death, and justification for actions sought, there might not be a single best option. Parents and medical staff are likely to have differing understandings of the child’s condition and prognosis, together with varying interpretations of moral and ethical values and beliefs involved.